Interventions delivered by nurses in adult outpatient psychiatric care: An integrative review. Issue 9 (31st July 2019) - Ameel, Maria; Kontio, Raija; Välimäki, Maritta
Accessible summary: What is known on the subject?: In many countries, the majority of psychiatric care is being delivered in an outpatient setting and the proportion of outpatients is increasing on a global level. Nurses are the largest workforce in psychiatric care, but their role has been said to be difficult to define. According to our knowledge, there are no previous reviews focusing on nurse‐delivered interventions in the adult psychiatric outpatient setting. What this paper adds to existing knowledge?: This review summarizes nurse‐delivered interventions identified in the research literature and describes these systematically. Analysing all the identified interventions using the Nursing Interventions Classification, we conclude that the emphasis of nurse‐delivered interventions in psychiatric outpatient care is on interventions aiming at improving the functioning of both patients and their family members by building on their own strengths. These findings differ from those presented in a review on inpatient psychiatric nursing. There are several clinical trials describing nurse‐delivered evidence‐based treatments, such as psychoeducation for patients and their family members in the case of patients diagnosed with schizophrenia and bipolar disorder. The quality of randomized controlled trials was higher than in earlier reviews describing psychiatric nursing interventions in general or in connection with a specific patient group. Further clinical trials are needed to describe the role of nurses in the care of patients diagnosed with depression and in the use of web‐based interventions. Additionally, it would be important to study what supports, and on the other hand hinders, the role of nurses in delivering evidence‐based treatments at the clinical level. What are the implications for practice?: Nurses can play a central role in responding to the growing demand for evidence‐based practices in adult outpatient psychiatry, by delivering treatments for patients and family members. It is important that both nursing education and clinical practices recognize and support this role. Abstract: Introduction: According to our knowledge, there are no previous reviews on nurse‐delivered interventions in the adult psychiatric outpatient setting. Aim: To identify and systematically describe and analyse nurse‐delivered interventions based on research literature. Method: An integrative review. Results: This review included 60 studies, of which 46 were intervention studies, including 40 clinical trials. The most common patient groups were patients diagnosed with schizophrenia and bipolar disorder. The nursing interventions described in the studies resembled a total of 68 interventions from the Nursing Interventions Classification. The treatment delivery methods varied and treatments often lacked a clear theoretical background. Implications for practice: The core of nurse‐delivered interventions identified in research literature in psychiatric outpatient care is on interventions aiming at improving the functioning of both patients and their family members by building on their own strengths. These findings differ from the interventions identified in a review describing nursing in the inpatient setting. There are high‐quality clinical trials describing nurse‐delivered treatments for patients diagnosed with schizophrenia and bipolar disorder. These include evidence‐based treatments such as psychoeducation. Understanding of how these treatments are transferred in clinical practice is missing. Clinical trials describing nurse‐delivered web‐based interventions and interventions for patients diagnosed with depression are needed.